The Future of The Workforce: Economic Structural Change in The Age of Automation and Al - Olyvia Rosalia; Firayani; Arief Fahruri (PT. Anagata Sembagi Education, 2025)
The development of technology, particularly in the fields of automation and artificial intelligence (AI), has led to significant structural changes in the global labor market and economy. This study aims to analyze the transformational impact of automation and AI on economic structures and their implications for the future of the workforce. Using a descriptive-qualitative approach and literature analysis along with secondary data, this research finds that the shift from a manufacturing-based economy to a digital and knowledge-based economy has caused disruptions to traditional jobs. Many routine jobs are now being replaced by technology, while demand for digital and analytical skills is rising sharply. The skills gap has become a major challenge, as much of the workforce is unprepared for the demands of the digital age. This study also highlights the importance of government policy, the role of businesses, and the education system in supporting reskilling and upskilling programs. The findings are expected to contribute to the formulation of adaptive strategies that respond to the changing economic structure in the era of automation and AI.